Development of the Competency Indicators for 21st Century of Teacher for Students with Special Needs - bunjongkarn, suchatth (Journal of Vocational Education in Agriculture, 2023)
The objective of this research was to develop the competency indicators for 21st century of teacher for students with special needs. The samples of this research were 33 specialists selected by purposive sampling technique. A questionnaire was used for collecting data based on Delphi technique. Data was analyzed by frequency distributions, median, mode, differences between median and mode, interquartile range and consistency consideration. The resultsrevealed that the competency indicators for 21st century of teacher for children with special needs consisted of 1) eight indicators forthe curriculum implementation and development aspect 2) eight indicators for the learning design aspect 3) nine indicators for the learning procedure aspect 4) six indicators for media innovation and technology for the learning management aspect 5) five indicators for the evaluation and assessment aspect 6) ten indicators for the classroom administration and management aspect 7) seven indicators for the research for learner development aspect and 8) nine indicators for the character of teacher aspect.